BANKRUPTCY OF INDIVIDUALS IN UZBEKISTAN: THE NEED TO IMPLEMENT AND POSSIBLE LEGAL MODELS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article substantiates the relevance of introducing the institution of personal bankruptcy in the Republic of Uzbekistan. Foreign legal models are analyzed, key issues related to the absence of such an institution are identified, and recommendations are made for the formation of national legislation, taking into account the socio-economic conditions of the country.